Alopecia: Updated management - Mia, Mohammad Tariquzzaman (Bangladesh Journal of Medicine, 2024)
Hair is of high aesthetic value in human. Loss of hair is called alopecia. It is a common and complex concern causes frustration, negetive emotion and lack of confidence. Normal daily hair loss is about 100 to 150.Causes of Alopecia are Non Scarring alopecia, pattern alopecia /Androgenetic Alopecia, Unpattern alopecia - Alopecia areata, Telogen effluvium, anagen effluvium, Traction alopecia due to hair style, hair shaft damage by hot air dryers and by hair Straightening and Other causes:- Alopecia syphilitica, diabetesmellitus, hypothyroidism,anaemia, seborrheic dermatitis, psoriasis. Scarring alopecia are Lichen planopilaris, pseudopelade, DLE, Folliculitis decalvans, infections. Diagnostic approach to hair loss : step-1 - History of the hair problem , step-2 - obtain a through medical history, step-3 - Examination of scalp and hair and step - 4- Diagnostic tests are Hair pull test, Dermoscopy,scalp biopsy. Lab tests-CBC, Ferritin, TIBC,TSH,Testosteron and step-5: Treatment: - according to the cause of hair loss.Medical treatment. Topical and intralesional steroid, topical Minoxidil, tacrolimus, finasteride, spironolactone. Updated medical treatment: Tofacitinib. Updated procedural treatment( Procedure): - PRP therapy, Microneedling, Low level Laser therapy (LLLT), stem cell therapy, Hair transplant. Bangladesh J Medicine 2024; Vol. 35, No. 2, Supplementation:137